Программный комплекс МotorSolve: верификация параметров и характеристик вентильного двигателя с постоянными магнитами - Рымша, Виталий Викторович; Радимов, Игорь Николаевич; Гулый, Михаил Викторович; Меркулов, Игорь Викторович (Национальный технический университет "Харьковский политехнический институт", 2019)
Рассмотрены некоторые возможности программного комплекса MotorSolve для моделирования и анализа вентильных двигателей с постоянными магнитами. Представлены результаты расчета параметров и характеристик вентильного двигателя с известными геометрическими размерами и обмоточными данными статора. Результаты расчета сопоставлены с результатами экспериментальных исследований.

Purpose.The purpose of this paper isto include comparison of results of the modeling and calculation in the Mentor Siemens software MotorSolve and experimentof the brushless permanent magnet motor. Methodology. Numerical investigation using licensed software MotorSolve is performed. Calculations of motor parameters and characteristics are made using Finite Element Method. The experimental investigations were made on the hysteresis dynamometer AHD-603. Results. The results of the investigations show that the calculations of the parameters and characteristics of the motor in MotorSolve software almost match with the results of the experiments. Practical value.The high efficiency of the MotorSolve software for the modeling, calculation and research of the brushless permanent magnet motors are confirmed.
MotorSolve software package: verification of parameters and characteristics of the brushless permanent magnet motor
Keywords: обмоточные данные статора; экспериментальные исследования; stator winding data; experimental investigations